Respostas

2014-04-25T12:46:23-03:00
A)     I) X+Y=-6
       II) X-Y=  1
     
        2X= -5 =>   X= -5/2
aplic. x em 1)
  I) X+Y=-6 =>  -5/2 + Y= -6
                       Y=-6+5/2
                         Y =  (-12+5)/2 =  -7/2
S={X= -5/2 , Y= -7/2}

b)  I) 2x-5y=3                          I) 2x-5y=3
    II)  x - y =-1   mut. p/ (-5)     II) -5x+5y=+5

                                               -3x = 8
                                                   x= - 8/3   aplic. X em I)
                                       2X-5Y=3 , P/ X=-8/3
                                     2(-8/3) -5Y =3
                                      -16/3 - 5Y = 3
                                           -5Y = 3+16/3
                                         -5Y =  (9+16)/3
                                        -5Y = 25/3
                                          Y= - 25/15 SIMPLIFICANDO POR 5
                                          Y = - 5/3
                                    S={X=-8/3 ,Y= -5/3}

       
1 1 1